Respuesta :
Question:
Which expression is equivalent to
[tex]\frac{\sqrt{2}}{\sqrt[3]{2}}[/tex]
Answer:
[tex]\frac{\sqrt{2}}{\sqrt[3]{2}} =2^{\frac{1}{6}} = \sqrt[6]{2}[/tex]
Step-by-step explanation:
Given
[tex]\frac{\sqrt{2}}{\sqrt[3]{2}}[/tex]
Required
Simplify
From laws of indices;
[tex]\sqrt[n]{x} =x^{\frac{1}{n}}[/tex]
So, the expression can be rewritten as
[tex]\frac{\sqrt{2}}{\sqrt[3]{2}} = \frac{{2^{\frac{1}{2}}}}{2^{\frac{1}{3}}}[/tex]
Also, from laws of indices
[tex]\frac{x^a}{x^b} = x^{a-b}[/tex]
So, the expression is further solved to:
[tex]\frac{\sqrt{2}}{\sqrt[3]{2}} =2^{\frac{1}{2} - \frac{1}{3}[/tex]
Solve exponents as fraction
[tex]\frac{\sqrt{2}}{\sqrt[3]{2}} =2^{\frac{3-2}{6}}[/tex]
[tex]\frac{\sqrt{2}}{\sqrt[3]{2}} =2^{\frac{1}{6}}[/tex]
This can be rewritten as
[tex]\frac{\sqrt{2}}{\sqrt[3]{2}} =2^{\frac{1}{6}} = \sqrt[6]{2}[/tex]
The expression equivalent to given expression is [tex]\sqrt[6]{2} [/tex].
Given expression is, [tex]\frac{\sqrt{2} }{\sqrt[3]{2} } [/tex]
Expression can be written as,
[tex]\frac{\sqrt{2} }{\sqrt[3]{2} } =\frac{2^{1/2} }{2^{1/3} } =2^{\frac{1}{2}-\frac{1}{3} } \\ \\ 2^{\frac{1}{2}-\frac{1}{3} } =2^{\frac{1}{6} }=\sqrt[6]{2} [/tex]
Learn more:
https://brainly.com/question/15968618